The orphan receptor GPR88 blunts the signaling of opioid receptors and multiple striatal GPCRs - Thibaut Laboute; Jorge Gandía; Lucie P Pellissier; Yannick Corde; Florian Rebeillard; Maria Gallo; Christophe Gauthier; Audrey Léauté; Jorge Diaz; Anne Poupon; Brigitte L Kieffer; Julie Le Merrer; et al. (eLife, 2020)
GPR88 is an orphan G protein-coupled receptor (GPCR) considered as a promising therapeutic target for neuropsychiatric disorders; its pharmacology, however, remains scarcely understood. Based on our previous report of increased delta opioid receptor activity in Gpr88 null mice, we investigated the impact of GPR88 co-expression on the signaling of opioid receptors in vitro and revealed that GPR88 inhibits the activation of both their G protein- and β-arrestin-dependent signaling pathways. In Gpr88 knockout mice, morphine-induced locomotor sensitization, withdrawal and supra-spinal analgesia were facilitated, consistent with a tonic inhibitory action of GPR88 on µOR signaling. We then explored GPR88 interactions with more striatal versus non-neuronal GPCRs, and revealed that GPR88 can decrease the G protein-dependent signaling of most receptors in close proximity, but impedes β-arrestin recruitment by all receptors tested. Our study unravels an unsuspected buffering role of GPR88 expression on GPCR signaling, with intriguing consequences for opioid and striatal functions.